1982
DOI: 10.1007/bf01666910
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile and cytotoxin in feces of patients with antimicrobial agent-associated pseudomembranous colitis

Abstract: Thirty patients with antimicrobial agent-associated pseudomembranous colitis (PMC) were studied for the presence of Clostridium difficile and its cytotoxin in feces. Either colonoscopy or barium enema radiography was required in three patients for the diagnosis of PMC because of nondiagnostic findings at sigmoidoscopy. Both the organism and cytotoxin were detected in 27 of the 30 patients; Staphylococcus aureus was excluded as the cause of PMC in two of the remaining patients. Eighteen of 19 patients with C. d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
2

Year Published

1985
1985
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 13 publications
0
47
2
Order By: Relevance
“…Differences in the levels of production of toxins TcdA and TcdB alone cannot account for the wide spectrum of clinical presentations. Georges et al (21) reported that there were no significant differences between clinical presentations according to the titer of the cytotoxin. Similarly, there was no correlation between virulence in a hamster model of AAC and the production of TcdA and TcdB in vitro (12).…”
Section: Discussionmentioning
confidence: 98%
“…Differences in the levels of production of toxins TcdA and TcdB alone cannot account for the wide spectrum of clinical presentations. Georges et al (21) reported that there were no significant differences between clinical presentations according to the titer of the cytotoxin. Similarly, there was no correlation between virulence in a hamster model of AAC and the production of TcdA and TcdB in vitro (12).…”
Section: Discussionmentioning
confidence: 98%
“…However, in 1978, C. difficile was identified as the primary cause of pseudomembranous colitis and shown to be a primary isolate from the feces of patients undergoing clindamycin treatment (10,57). These seminal observations were followed by a series of reports which further showed a strong correlation between pseudomembranous colitis, antibiotic therapy, C. difficile colonization, and cytotoxin production (6,11,16,36,56,116,166,183). Collectively, these original studies and observations revealed C. difficile as an emerging pathogen capable of causing severe gastrointestinal disease in individuals undergoing antibiotic therapy.…”
Section: Introductionmentioning
confidence: 97%
“…Clostridium difficile has emerged as the most important cause ofantibiotic-associated colitis in animals ( 1, 2) and humans (3,4) and is one of the most commonly diagnosed nosocomial infections (5). This gram-positive obligate anaerobe produces two protein exotoxins: toxin A and toxin B. Toxin A is a 308-kD (6) enterotoxin that elicits intestinal fluid secretion and inflammation, causes severe destruction of villi, and increases permeability in adult rabbit and guinea pig ileum (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%